Social Media in the promotion of cultural content in television, analysis of case in Ecuador. - Suing, Abel (2022)
The cultural and educational programs aimed at the television of Ecuador are analyzed in relation to the use of social media, in a context of new legislation. The purpose is to establish the integration in social media from Facebook and Twitter in the programs Educa TV, Aprendamos y Expresarte.. The instruments used are the rate of participation in Facebook and Twitter Following - Followers ratio, in addition to interviews with involved. It is concluded that the cultural content tend to increase, the hearings do not build collectively; and, producers should not fail to create content, community, conversation.